Acute effects of battle rope exercise on performance, blood lactate levels, perceived exertion, and muscle soreness in collegiate basketball players - Chen, W. H.; Yang, W. W.; Lee, Y. H.; Wu, H. J.; Huang, C. F.; Liu, C. (The Journal of Strength and Conditioning Research, 2020)
This study investigated the acute effects of battle rope (BR) exercise on basketball players' performance, blood lactate levels, rating of perceived exertion (RPE), and perceived muscle soreness. Fifteen well-trained Division-I male basketball players underwent the same test procedure at baseline, before BR exercise (30 minutes of rest after the baseline test), and after BR exercise. The 30-minute experimental protocol comprised 6 BR exercises at a work-to-rest ratio of 1:2 (20-second exercise and 40-second rest). Shooting accuracy, basketball chest pass speed, countermovement jump (CMJ) height, blood lactate levels, RPE (Borg Category-Ratio-10 scale), and perceived muscle soreness (visual analog scale, 0-100 mm) were measured in each test. The results indicated no change for any variables between baseline and before BR exercise. After BR exercise, performance decrements (p < 0.05) were recorded in shooting accuracy (16.9%) and basketball chest pass speed (9.1%), but no significant changes were observed for CMJ height. Battle rope exercise caused increases in blood lactate levels (13.6 mmol·L-1), RPE (9.9), and perceived muscle soreness (upper-limb: 63-67 mm; trunk: 43-68 mm; and lower-limb: 45-52 mm). In conclusion, BR exercise is physically demanding on the upper body, resulting in decreased performance in shooting accuracy and basketball chest pass speed. Battle rope exercise may not be beneficial before a practice or game because it triggers acute exercise-induced performance decrements and fatigue. However, BR exercise may be suitable for basketball training sessions in which the objective is to strengthen technical skills under fatiguing conditions.